Construction and validation of a glioblastoma prognostic model based on immune-related genes - Huang, Kate; Rao, Changjun; Li, Qun; Lu, Jianglong; Zhu, Zhangzhang; Wang, Chengde; Tu, Ming; Shen, Chaodong; Zheng, Shuizhi; Chen, Xiaofang; Lv, Fangfang (Frontiers in Neurology, 2022)
Abstract Background: Glioblastoma multiforme (GBM) is a common malignant brain tumour with high mortality. It is urgently necessary to develop a new treatment because traditional approaches have plateaued. Purpose: Here, we identified an immune-related gene (IRG)-based prognostic signature to comprehensively define the prognosis of GBM. Methods: Glioblastoma samples were selected from the Chinese Glioma Genome Atlas (CGGA). We retrieved IRGs from the ImmPort data resource. Univariate Cox regression and LASSO Cox regression analyses were used to develop our predictive model. In addition, we constructed a predictive nomogram integrating the independent predictive factors to determine the one-, two-, and three-year overall survival (OS) probabilities of individuals with GBM. Additionally, the molecular and immune characteristics and benefits of ICI therapy were analysed in subgroups defined based on our prognostic model. Finally, the proteins encoded by the selected genes were identified with liquid chromatography-tandem mass spectrometry and western blotting (WB). Results: Six IRGs were used to construct the predictive model. The GBM patients were categorised into a high-risk group and a low-risk group. High-risk group patients had worse survival than low-risk group patients, and stronger positive associations with multiple tumour-related pathways, such as angiogenesis and hypoxia pathways, were found in the high-risk group. The high-risk group also had a low IDH1 mutation rate, high PTEN mutation rate, low 1p19q codeletion rate and low MGMT promoter methylation rate. In addition, patients in the high-risk group showed increased immune cell infiltration, more aggressive immune activity, higher expression of immune checkpoint genes, and less benefit from immunotherapy than those in the low-risk group. Finally, the expression levels of TNC and SSTR2 were confirmed to be significantly associated with patient prognosis by protein mass spectrometry and WB. Conclusion: Herein, a robust predictive model based on IRGs was developed to predict the OS of GBM patients and to aid future clinical research.